Book Review (Orfeu, 2019)
This text presents a review of the book Music Education in an Age of Virtuality and Post-Truth, by Canadian University Professor Paul G. Woodford (2019). The book stitches John Dewey’s pragmatism with George Orwell’s ideas about mass societies in order to understand the impact that certain actions of 21st century politicians can have on the field of Education, the Arts and the Humanities. In conclusion, similar examples of politicians from Brazil and Latin America are offered, supported by the ideas of Newton Duarte and what he called The Curriculum in times of Belligerent Obscurantism.
Keywords: Trump; Newton Duarte; Arts; Post Truth; Virtual; Music Education